A Survey of the Nexus between the Group Theory in Public Policy-Making; and Diplomacy and Diplomatic Practices; and Its Impact on International Public Administration - MASUMBE, Peter SAKWE (Advances in Social Sciences Research Journal, 2021)
This article seeks to discern the nexus between the group theory in public policy-making in domestic politics; and diplomacy and diplomatic practices in international relations. Apparently, diplomacy and diplomatic practices, though strands of international relations, pivot on group theory’s doctrines. Herein, I argue that, there exist a nexus between the group theory, diplomacy and diplomatic practices, which fashions the character of international public administration. Given the literature dearth in this domain, I offer a framework based on Charles Lindblom’s Incrementalism and the Realist Theory to show how the nexus between the group theory of domestic politics; and diplomacy and diplomatic practices impacts international public administration. The research purpose is to boost deeper theoretical and empirical understanding of public administration, since the group theory aims at causing group equilibrium amongst competing groups in domestic politics; while diplomacy promotes group’s (state) interest (power) over another group’s (state) interest (power) in international politics.